Realignment and Party Revival. - Paulson, Arthur C. (Spring;Political Science., 1998)
Keywords: dept.psc; faculty_collection; sabbatical_report

Przemysl, Poland; a Study in Regard to Its East Europe/West Europe Frontier. - Best, Paul J. (1997)
Keywords: dept.psc; faculty_collection; sabbatical_report

Affirmative Action in Higher Education. - Rai, Kul B. (Spring;Political Science., 1996)
Keywords: dept.psc; faculty_collection; sabbatical_report

Center-Right Political Coalitions in American National Politics. - Weed, Clyde (1996)
Keywords: dept.psc; faculty_collection

Affirmative Action in Higher Education. - Critzer, John (1995)
Keywords: dept.psc; faculty_collection; sabbatical_report

Greek Civil War of 1946-1949. - Iatrides, John O. (1992)
Keywords: dept.psc; faculty_collection; sabbatical_report

Governing Through Turbulence: Leadership and Change in the Late 20th Century. - Walsh, David (1991)
Keywords: dept.psc; faculty_collection

The Lemko-Rusyns in the 20th Century: A Study in the Development of National Consciousness. - Best, Paul J. (1988)
Keywords: dept.psc; faculty_collection; sabbatical_report

Public Activities and Studies Related to the Social Role of People with Disabilities. - Gelbach, Robert (1988)
Keywords: dept.psc; faculty_collection; sabbatical_report

America in the 21st Century: Challenges and Opportunities in Domestic Politics - Rai, Kul B.; Walsh, David F.; Best, Paul J. (Prentice Hall, 1998)
Keywords: 1989-; Political planning; Politics and government; United States; United States; dept.psc; faculty_collection

Carpatho-Slavic Studies. - Best, Paul J.; Carpatho-Slavic Studies Group (Carpatho-Slavic Studies Group, 1995)
Keywords: Carpatho-Rusyns; History; Periodicals; dept.psc; faculty_collection

Governing Through Turbulence: Leadership and Change in the Late Twentieth Century - Walsh, David F.; Best, Paul J.; Rai, Kul B. (Praeger, 1995)
Keywords: Case studies; Comparative government; Political leadership; dept.psc; faculty_collection

Political Alignment in the French National Assembly, 1789-1791 - Applewhite, Harriet Branson (Louisiana State University Press, 1993)
In this richly detailed study Harriet B. Applewhite analyzes the political alignment and loyalties of the deputies elected to the Estates General/National Assembly between 1789 and 1791. Her purpose is to understand how these men shaped the struggle that transformed France's constitutional structure and invented its modern political practices., To gauge the deputies' political alignments, Applewhite establishes categories based on their voting records, club memberships, signatures on protest lists, assessments by contemporary observers, and other evidence. She then arranges on a left-to-right scale all 1,318 of these individuals. For a selected group of deputies she uses published political pamphlets and biographical records not only to assess and compare their attitudes on issues concerning political legitimacy and political participation but also to establish and analyze connections between these attitudes and actual political behavior., Applewhite's investigation focuses on the origins of the deputies' understanding of French national unity, the nature and basis of the fierce partisan battles that raged in the National Assembly, and the changes in political institutions and practices that were handed down to postrevolutionary France. Contrary to the converging-elites theory popular among many students of the French Revolution, Applewhite finds that membership in one of the three estates of the Old Regime - the clergy, the aristocracy, and the commonalty - channeled the early careers of future deputies, their subsequent political opportunities, and their responses to the power struggles of the National Assembly., Applewhite defines two key legacies of the first National Assembly for the future of French legislative politics: first, a reluctance to compromise and an absence of trust that developed among participants at the outset and hardened throughout the twenty-eight months of the assembly; second, the development of a left, center, and right political culture within the National Assembly and a style of conflict that pulled both leaders and followers away from the center. This meticulously researched and carefully written work makes a significant and lasting contribution to the study of the French Revolution and points to new avenues of inquiry.--(Source of description unspecified.)
Keywords: 1789-1799; 18th century; France; France; France. Assemblée nationale constituante (1789-1791); History; History; France. États généraux; History; Legislators; Politics and government; award_winner; dept.psc; faculty_collection

Women and Politics in the Age of the Democratic Revolution - Applewhite, Harriet Branson; Levy, Darline Gay (University of Michigan Press, 1990)
Keywords: 18th century; 18th century; Revolutions; 18th century; Women; Europe; History; Political activity; United States; Women; dept.psc; faculty_collection

Politics in Three Worlds: An Introduction to Political Science - Best, Paul J.; Rai, Kul B.; Walsh, David F. (Wiley, 1986)
Keywords: Political science; Comparative government; Comparative economics; dept.psc; faculty_collection

The Morning Cometh: 45 Years with Anatolia College - Compton, Carl C.; Iatrides, John O.; Compton, William R. (Aristide D. Caratzas, 1986)
Keywords: 20th century; High school teachers; Biography; Biography; Anatolia College; Biography; High school teachers; Compton, Carl C; Anatolia College; Faculty; Greece; History; Turkey; dept.psc; faculty_collection

Greek-American Relations: A Critical Review - Couloumbis, Theodore A.; Iatrides, John O. (Modern Greek research series, 1980)
Keywords: Foreign relations; Greece; Greece; United States; award_winner; dept.psc; faculty_collection

Women in Revolutionary Paris, 1789-1795 - Levy, Darline Gay; Applewhite, Harriet Branson; Johnson, Mary Durham (University of Illinois Press, 1979)
"Almost 200 years ago, the women of revolutionary Paris were demanding legal equity in marriage; educational opportunities for girls, including vocational training ; public instruction, licensing, and support for midwives; guarantees for women's rights to employment; and an end to the exclusion of women from certain professions. The editors have uncovered, translated, and annotated sixty documents which shed light on these and other socioeconomic struggles by women and their impact on the French Revolutionary era. This work makes a significant contribution to the growing appreciation of the role of women in history, politics, ideology, and social change."--Back cover.
Keywords: France; History; Paris; Political activity; Revolution, 1789-1799; Sources; Sources; France; Sources; Women; Women's rights; dept.psc; faculty_collection

Revolt in Athens; the Greek Communist "Second Round," 1944-1945, - Iatrides, John O. (Princeton legacy library, 1972)
Keywords: 1935-1967; Greece; Greece; Kommounistiko Komma Helladas; World War, 1939-1945; Politics and government; Underground movements; dept.psc; faculty_collection

The development of non-social insurance in Imperial Russia: a dissertation submitted in partial fulfillment of the requirements for the degree of master of arts in the department of history at Fordham University - Best, Paul J. (Thesis M.A. -- Fordham University., 1965)
Keywords: History; Insurance; Russia; dept.psc; faculty_collection

The origins and development of insurance in imperial and Soviet Russia: a dissertation in the Department of Government and International Relations submitted to the faculty of the Graduate School of Arts and Science in partial fulfillment of the requirements for the degree of Doctor of Philosophy at New York University - Best, Paul J. (Thesis Ph.D. -- New York University., 1965)
Keywords: History; Insurance; Russia; dept.psc; faculty_collection

Book Review: Prospects for Change in Socialist Systems: Challenges and Responses. Edited by Charles J. Bukowski and Mark A. Cichock. New York: Praeger, 1987. 151p. $34.95. - Best, Paul J. (American Political Science Review, 1989)
Keywords: book review; book.review; dept.psc

UN voting data - Rai, Kul B (Journal of Conflict Resolution, 1982)
Keywords: dept.psc

Foreign aid and voting in the UN general assembly, 1967—1976 - Rai, Kul B (Journal of Peace Research, 1980)
This paper examines the relationship between foreign (economic) aid and the General Assembly votes for the period 1967-76. The countries included in this study are the United States, the Soviet Union, and those of their aid recipients which are considered less developed. Two related hypotheses, one on the use of aid as an inducement and the other as a reward or a punishment, are tested. The methods used are Index of Agreement, devised by Arend Lijphart, and Pearson's r. The findings indicate that the American aid is more effective as an inducement and the Soviet aid is more effective as a reward or a punishment. The former has a closer association with the General Assembly votes from 1967-73 than in later years. Economic aid is increasingly used by the United States more to serve its security interests in the Middle East than for any other purpose, and it is possible that not so much of a return for the American aid is expected in the UN as was the case earlier. © 1980, Sage Publications. All rights reserved.
Keywords: dept.psc

Lijphart's IA and pearson's r for studying un voting - Rai, Kul B (Comparative Political Studies, 1974)
Keywords: dept.psc

Foreign policy and voting in the UN general assembly - Rai, Kul B (International Organization, 1972)
Keywords: dept.psc

Blacks and women in public higher education: Political and socioeconomic factors underlying diversity at the state level - Critzer, John W.; Rai, Kul B. (Women & Politics, 1998)
In this paper, we analyze the political and socioeconomic factors that may be associated with black and female employment in American public higher education. We develop representation ratios for black females, black males, white females, and white males who serve as full-time faculty members in public higher education institutions in the American states. Our analysis shows that region, in this case the South, provides the best indicator for black female and black male faculty employment in public higher education. The percentage of black state legislators is also associated with black faculty employment. For white women, we found that although they are well represented on faculties, their numbers do not reach their share of the population. None of the variables examined explained their employment as faculty members. Women as a group had a particularly weak presence in state legislatures and continue to have less political power than blacks and white males. We suggest a number of possible avenues for future research to clarify these findings.
Keywords: dept.psc; ⚠️ Invalid DOI

Racial and gender income inequality in the American states - Critzer, John W (Race and Society, 1998)
The purpose of this article is to uncover the political factors associated with greater income parity for black men, black women, and white women relative to white men in the American states. Variables are constructed for federal, state, and local government employment, state electoral competition, federal procurement, black state legislators, and women state legislators along with a number of socioeconomic factors. It is discovered that the political variables carry less weight than the socioeconomic ones. These findings raise questions about the future prospects for increased earnings parity for minorities and women as previous federal efforts to eliminate racial and gender discrimination appear to have been weakened and state political factors have little relationship with greater income equality.
Keywords: dept.psc

Poland's Journalists: Professionalism and Politics. By Jane Leftwich Curry. New York: Cambridge University Press, 1990. 302p. $54.50. - Best, Paul J. (American Political Science Review, 1991)
Keywords: dept.psc